Case Report: Full-Endoscopic Surgery for Bullet Wounds of the Spine: A Report of Three Cases - Kravtsov, Maxim N.; Manukovsky, Vadim A.; Bulyshchenko, Gennadiy G.; Mirzametov, Saidmirze D.; Byvaltsev, Vadim A. (Frontiers in Surgery, 2022)
Objectives. To determine the feasibility and evaluate effectiveness of full-endoscopic surgery in gunshot wound of the spine. Methods. Three clinical cases of lumbar and thoracic spine bullet wounds made by firearms and traumatic weapons are described. Percutaneous endoscopic surgery was performed to extract bullet from the spinal canal. The results are compared to the data from literature. Results. Percutaneous endoscopic approach to spinal canal with a possibility to extract a bullet, decompression of nerve roots, defect closure of the dura mater is demonstrated. Conclusion. Good clinical outcomes allows to recommend percutaneous endoscopic surgery to manage similar lumbar and thoracic spine bullet wounds at the stage of specialized medical care.